DEVELOPMENT OF LOGICAL THINKING IN THE PRIMARY CLASSES - Dinora TOGAEVA; Lobar MUKHTAROVA (Scholar Express Journal, 2024)
This article is devoted to the study and development of logical thinking in primary school children. Logical thinking is an important cognitive process that contributes to the development of analytical and problem-oriented skills in children. The purpose of the study is to identify effective methods and approaches to the development of logical thinking in children of primary age
Keywords: logic; thinking; logical tasks